تأثير المعالجة الانعكاسية على المؤشرات القلبية والتنفسية لدى المرضى الخاضعين لجراحة القلب المفتوح قبل وبعد إجراء الجراحة - غزال, سوسن; معروف, سمر (Latakia University Journal -Medical Sciences Series, 2018)
Open heart surgery is one of the most stressful incidents which may occur in patients life, that leading to the occurrence of changes in the cardiac and respiratory indicators patients. Objective : aim of this study was to study the effectof reflexotherapy on respiratory and cardiac indexes in patients pre and post open heart surgery. Material and method : This study was performed on patients who had open heart surgery and had the inclusion criteria for entering the study in ICU in Bassel Center for disease and heart surgery in Lattakia. A sample of 30 male and female patients was randomly divided into two groups: control group, experimental group. Th experimental group received foot ,hand and ear reflexotherapy before and after surgery. Results : This study showed that, and foot ,hand and ear reflexotherapytogether was the most effective in improve respiratory and cardiac indexes levels and recommended about importance of reflexotherapyfor patients pre and post open heart surgery. تعد جراحة القلب المفتوح من أكثر الأحداث المجهدة التي يواجها المرضى والتي تؤدي إلى اضطرابات في المؤشرات القلبية والتنفسية. الهدف: هدفت الدراسة إلى تقييم تأثير المعالجة الإنعكاسية للقدم واليد والأذن على المؤشرات القلبية والتنفسية لدى مرضى جراحة القلب المفتوح قبل وبعد الجراحة. أدوات البحث وطرائقه:أجريت هذه الدراسة على عينة مؤلفة من (30) مريضاً ذكوراً وإناثاً موزعين على مجموعتين (المجموعة التجريبية :تطبيق المعالجة الإنعكاسية على القدم, اليدوالأذن، والمجموعة الضابطة) في وحدة العناية المشددة فيمركز الباسل لأمراض وجراحة القلب فيمحافظة اللاذقية، جُمعت البيانات باستخدام استمارة تتضمن البيانات الشخصية والصحية واستمارة تتضمن تقييم المؤشرات القلبية والتنفسية . النتائج: خلُصت النتائج إلى أن المعالجة الانعكاسية للقدم واليد والاذن كان له الآثر الأكبر على تحسين مستويات المؤشرات القلبية والتنفسية ، وأوصت الدراسة بضرورة تطبيق المعالجة الانعكاسية للمرضى الخاضعين لجراحة القلب المفتوح.